Kasus Langka Iskemia Tungkai Akut Vasospastik - Naesilla, Naesilla; Suryono, Suryono (Jurnal Kardiologi Indonesia, 2021)
Background: Acute limb ischemia (ALI) requires immediate treatment to maintain limb viability and prevent morbidity and mortality. Nevertheless, vasospastic acute limb ischemia on limb arteries is rarely reported. Case Illustration: This article reported a 37-year-old woman with sudden pain in her left leg and foot. The absence of peripheral pulsation of the left dorsalis pedis artery and popliteal artery were noted. Her foot was cold and clammy with decreased oxygen saturation in the left toes. The symptoms were partially improved following heparinization therapy. Angiography was conducted, and it revealed the spasms of the left popliteal and dorsalis pedis arteries with no sign of acute embolism or thrombosis. Arterial vasospasm is a rare cause of acute limb ischemia. A theoretical etiology of this vasospasm might be a secondary Raynaud's phenomenon. The associated factors were female, pre-menopausal age, the use of combined injectable contraception containing estrogen, and exposure to cold temperatures. Conclusion: This case report emphasizes the necessity to consider all possible causes in ALI-presenting cases to provide adequate therapy and prevent limb death.